2017
DOI: 10.1523/eneuro.0215-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Online Motor Control Is Intact in Parkinson’s Disease With and Without Perceptual Awareness

Abstract: In the double-step paradigm, healthy human participants automatically correct reaching movements when targets are displaced. Motor deficits are prominent in Parkinson’s disease (PD) patients. In the lone investigation of online motor correction in PD using the double-step task, a recent study found that PD patients performed unconscious adjustments appropriately but seemed impaired for consciously-perceived modifications. Conscious perception of target movement was achieved by linking displacement to movement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Congruently, PD patients performed corrective saccades at a comparable level to healthy controls in a saccade double-step task (Merritt et al, 2017), although they also exhibited a larger number of averaging saccades (Bhutani et al, 2013).…”
Section: Preservation Of Eye Movements In Parkinson's Disease Is Stimulus and Task Specificmentioning
confidence: 88%
“…Congruently, PD patients performed corrective saccades at a comparable level to healthy controls in a saccade double-step task (Merritt et al, 2017), although they also exhibited a larger number of averaging saccades (Bhutani et al, 2013).…”
Section: Preservation Of Eye Movements In Parkinson's Disease Is Stimulus and Task Specificmentioning
confidence: 88%
“…The fact that conscious perception of target jump interferes with automatic motor control in PD [ 101 ] has been recently contested in [ 125 ]. Indeed, when the target jump is imposed at the movement onset, the akinesia in limb motion inevitably prolongs the period from target appearance to target displacement.…”
Section: Anomalies In Execution Of Upper Limb Tasksmentioning
confidence: 99%
“…This may disproportionately impact the performances of patients, since their long preparations do not favor quick re-modulation of the trajectory [ 126 ]. By using large target displacements during initial saccadic fixation to target, but still consciously perceived by the subjects, Merritt et al [ 125 ] ensured equivalent onsets of target displacement for PD and controls and demonstrated that automatic trajectory modifications were equivalent in both groups and were unaffected by dopaminergic therapy. This questioned the idea that BG actually mediate the online motor control.…”
Section: Anomalies In Execution Of Upper Limb Tasksmentioning
confidence: 99%
“…Preserved functions are also found when a movement trajectory has to be corrected online to account for a displacement of the movement target, a task that requires a sense of urgency (Desmurget et al, 2004). Congruently, PD patients performed corrective saccades at a comparable level to healthy controls in a saccade double-step task (Merritt et al, 2017), although they also exhibited a larger number of averaging saccades (Bhutani et al, 2013). In sum, there is consensus that eye movements can be spared in PD patients under some task and stimulus conditions.…”
Section: Introductionmentioning
confidence: 99%